Development and Validation of RP-HPLC Method For Simultaneous Estimation of Cefixime and Cloxacillin in Tablet Dosage Form - Wankhede, Ajit R (International Journal of Pharmaceutical & Biological Archive, 2010)
A rapid, sensitive and specific RP-HPLC method involving U.V detection was developed and validated for the estimation of Cefixime and Cloxacillin in tablet dosage form. The method was validated in terms of linearity, accuracy, precision, specificity, robustness, limit of detection and limit of quantitation. The mobile phase used acetonitrile: tetra-butyl ammonium hydroxide buffer in the ratio of 45:55 and pH adjusted to 4 with orthophosphoric acid. The detection of combined dosage form was carried out at 225 nm at constant flow rate of 1ml/min. Hydrochlorothiazide was used as internal standard. The retention time of Cefixime, Cloxacillin and hydrochlorothiazide were found 5.75 min, 11.90 min and 3.74 min respectively. Linearity was observed in 10-50 µg/ml for Cefixime (r2 = 0.9994) and 25–125 µg/ml for Cloxacillin (r2 = 0.9998). Detection limit for Cefixime and Cloxacillin is 0.05µg/ml and 0.18 µg/ml respectively and quantification limit for Cefixime and Cloxacillin is 0.15µg/ml and 0.11 µg/ml. The proposed method was successfully applied for the quantitative determination of Cefixime and Cloxacillin in tablet dosage form.